The Effect of Youtube Social Media Use on Student Learning Outcomes in Social Studies Class 9 SMPN 16 Mataram - Sakti, Hadi Gunawan; Maulana, Lalu Hazrin Dwifa (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2025)
Based on the results of observations made at SMPN 16 Mataram, researchers found problems faced specifically in social studies subjects, namely the lack of use of learning media that occurred at SMPN 16 Mataram in social studies subjects. There are only a few teachers who use learning media, while others still use textbooks, whiteboards and markers. The aim of this research is to determine the effect of using YouTube social media on the learning outcomes of class IX students at SMPN 16 Mataram for the 2024/2025 academic year. In this research, quantitative methods were used, the design used was a one group pretest-posttest experimental design. This research data collection technique uses test, observation and documentation methods. The results of this research show that there is an increase in learning outcomes in the learning process, this fact shows that the tcount value is greater than ttable (9.936>1.714). This is the alternative hypothesis (Ha) which states that there is an influence of the use of YouTube social media on student learning outcomes in social studies subjects for Class IX SMPN 16 Mataram for the 2024/2025 academic year. This research can be concluded that there is an influence of the use of YouTube social media on student learning outcomes in social studies subjects for Class IX SMPN 16 Mataram for the 2024/2025 academic year. Using learning media-based teaching materials can improve student learning outcomes as seen from the pretest-posttest of students who experience improvement. Keywords: Presentation Media, YouTube, Learning Results Â